Nudging primary care providers to expand the opioid use disorder workforce. (7th November 2021) - Domino, Marisa Elena; Sylvia, Sean; Green, Sherri
Abstract: Objective: To examine the responsiveness of primary care providers to pro‐social and financial incentives to participate in a learning collaborative for the treatment of opioid use disorder (OUD). Study setting: We conducted a statewide experiment in North Carolina from January 2019 to November 2019 to expand access to support for providers learning to treat opioid use disorder using different types of messaging and incentives. Study design: We randomly assigned 15, 835 primary care providers (physicians, nurse practitioners, and physician assistants) in North Carolina (NC) to receive one of four letters recruiting providers to participate in an online learning collaborative for providers learning to treat opioid use disorder. The four versions of the recruitment letters contained either pro‐social messaging, mention of financial reimbursement for time spent in the learning collaborative, both, or neither. Data collection: We created a primary data source, tracking provider responses to the recruitment letters and emails. Principal findings: We found a 47.5% greater ( p  < 0.05) response rate using pro‐social recruitment messaging that provided a greater description of the local conditions in each provider's region compared to the control group; this effect increased with higher overdose opioid death rates. Mention of financial reimbursement only modestly increased provider response rates. Some heterogeneity was observed by provider type, with NPs having the largest response to pro‐social messaging. Conclusions: Prosocial nudges had strong effects on efforts to enhance the behavioral health workforce in NC through participation in an ECHO for medication‐assisted treatment (MAT) learning collaborative. The prosocial approach can and should be employed by states and professional societies in their efforts to create training programs for medication for OUD (MOUD), in order to expand access to lifesaving treatments for opioid use disorder.